Facile Synthesis and Characterization of the Reduced Graphene Oxide/Co\(_3\)O\(_4\) Nanocomposite for Capacitive Application - Pham, Thi Nam; Nguyen, Thi Thom; Nguyen, Thi Thu Trang; Dinh, Thi Mai Thanh; Vo, Thi Kieu Anh; Nguyen, Anh Son; Tran, Dai Lam (Communications in Physics, 2020)
Reduced graphene oxide/Co\(_3\)O\(_4\) (rGO/Co\(_3\)O\(_4\)) were prepared by simple ultrasonic method from graphene oxide (GO) and Co(CH\(_3\)COO)\(_2\) precursor. The synthesized rGO/CO3O4 was thoroughly characterized by SEM/EDX, XRD, FTIR and BET. The obtained results indicate the presence of well-crystalized Co\(_3\)O\(_4\) nanoparticles onto the rGO nanosheets in the lamellar structure of rGO/Co\(_3\)O\(_4\). Despite slight decrease in BET specific surface area (from 389.9 m\(^2\)/g of rGO to 218.7 m\(^2\)/g of rGO/Co\(_3\)O\(_4\)), cyclic voltammetry studies show that the rGO/Co3O4 electrode exhibited high specific capacitance (95.8 F/ g at 50 mV/ s) with redox properties. The synthesized composites are expected to be a potential electrode candidate in supercapacitor as well as in hybrid capacitive deionization (HCDI) system for the desalination purpose.